The "Nazi menace" in Argentina : 1931 - 1947 - Newton, Ronald C. (Stanford Univ. Press, 1992)
One of the unanswered questions in the history of the 1930's and 1940's concerns just what the Nazis were up to in Argentina. Here was a country whose population was almost entirely European in origin and outlook, led by a conservative landed elite determined to retain power against the rising forces of socialism and "bolshevism." Here, too, was a substantial German-speaking minority numbering some quarter of a million. Could Argentina, then, have "gone Nazi"? This is the first complete, thoroughly researched investigation into the myth and reality of Nazi Germany's influence and activities in Argentina. It covers Nazi attempts to penetrate and convert Argentina's German-speaking population, to proselytize the Argentine military and right-wing political groups, and to influence the governments of the period